2021
DOI: 10.3390/foods10123129
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia Head Protein Hydrolysate Attenuates Scopolamine-Induced Cognitive Impairment through the Gut-Brain Axis in Mice

Abstract: The destruction of the homeostasis in the gut-brain axis can lead to cognitive impairment and memory decline. Dietary intervention with bioactive peptides from aquatic products is an innovative strategy to prevent cognitive deficits. The present study aimed to determine the neuroprotective effect of tilapia head protein hydrolysate (THPH) on scopolamine-induced cognitive impairment in mice, and to further explore its mechanism through the microbiota–gut-brain axis. The results showed that THPH administration s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown that scopolamine injections decreased the α-diversity, increased Firmicutes, and decreased Bacteroides [ 23 ]. Scopolamine injections have been demonstrated to positively correlate with Clostridium, Bifidobacterium, Ruminococcaceae_unclassified, Lachnospiraceae_unclassified, and Lactobacillus while being negatively related to Desulfovibrio, Akkermansia , and Blautia [ 23 ]. Scopolamine injections increase the intestinal permeability and induce memory impairment [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that scopolamine injections decreased the α-diversity, increased Firmicutes, and decreased Bacteroides [ 23 ]. Scopolamine injections have been demonstrated to positively correlate with Clostridium, Bifidobacterium, Ruminococcaceae_unclassified, Lachnospiraceae_unclassified, and Lactobacillus while being negatively related to Desulfovibrio, Akkermansia , and Blautia [ 23 ]. Scopolamine injections increase the intestinal permeability and induce memory impairment [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scopolamine injections have been demonstrated to positively correlate with Clostridium, Bifidobacterium, Ruminococcaceae_unclassified, Lachnospiraceae_unclassified, and Lactobacillus while being negatively related to Desulfovibrio, Akkermansia , and Blautia [ 23 ]. Scopolamine injections increase the intestinal permeability and induce memory impairment [ 23 , 24 ]. The present study also showed similar changes in the gut microbiota and memory function.…”
Section: Discussionmentioning
confidence: 99%
“…Donepezil is a potent acetylcholinesterase inhibitor, and the US FDA approved donepezil for dementia treatment, but its long-term efficacy and safety are unclear. Diet interventions such as protein hydrolysates have been studied for dementia prevention [ 25 ]. In the present study, donepezil was used as the Positive-control.…”
Section: Discussionmentioning
confidence: 99%
“…The gut–brain axis involves two-way biochemical signaling between the gastrointestinal tract and the central nervous system (CNS). The gut microorganisms contribute to the host’s energy metabolism, serum metabolites, and brain function through SCFA, secondary bile acids, amino acids, and neurotransmitters [ 25 , 28 ]. The dysbiosis of the gut microbiota decreasing Lactobacillus and Bifidobacterium species is related to neurodegenerative diseases [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are significant associations between gut microbiota and demyelination by the microglia in brain, suggesting that the crosstalk between gut-microbiota and brain-microglia could play a key role for clearing out the engrams [ 63 ]. In fact, the destruction of the homeostasis in the gut-brain axis could lead to cognitive impairment and memory decline [ 64 ].…”
Section: Innovative Praxis With Gut-brain-immune Axis For the Potenti...mentioning
confidence: 99%